Almonertinib plus chemotherapy versus almonertinib alone in second-line treatment of advanced non-small cell lung cancer with mutated epidermal growth factor receptor: a retrospective study - Fang, Xiaoxu; Xiang, Yan; Lu, Kaihua (Frontiers in Oncology, 2023)
Objective: This study mainly observes the efficacy and safety of almonertinib plus chemotherapy compared with almonertinib alone in the second-line treatment of advanced non-small cell lung cancer (NSCLC) with mutated epidermal growth factor receptor (EGFR). Methods: In this study, clinical data of 68 patients with advanced NSCLC who were treated in Jiangsu Provincial People's Hospital and Nanjing Chest Hospital between April 2020 and December 2022 were collected.Among them, the study group (n=30) received second-line almonertinib combined with platinum-based chemotherapy, while the control group (n=38) received almonertinib alone. The near-term and long-term effects and adverse events of the two groups were compared respectively. Results: The median follow-up time until 31 December 2022 was 16.3 months (95% CI: 11.32-21.34). Results of chi-square analysis showed no statistically significant difference in objective response rate (ORR) and disease control rate (DCR) between the study group and the control group (56.73% vs 55.3%, P>0.05; 100% vs 86.8%, P>0.05). Log-rank test comparing the two groups revealed that the median progression-free survival (mPFS) of the study group was significantly longer than that of the control group by 3.1 months (12.7 vs 9.6 months, P=0.01). Multivariate COX proportional risk model showed a statistically significant effect of treatment 删除了: Efficacy of almonertinib combined with chemotherapy versus almonertinib alone in secondline treatment of advanced non-small cell lung cancer 删除了: This study was conducted to observe the efficacy and safety of almonertinib combined with chemotherapy and almonertinib alone in second-line treatment of advanced nonsmall cell lung cancer (NSCLC) with epidermal growth factor receptor (EGFR) mutation and to analyze the relevant factors affecting patient outcomes.